Multiscale track-seabed dynamic interaction during deep-sea seabed mining across operational modes - Bin Zhu; Xianhao Xiu; Ying Lai; Yunmin Chen; Viroon Kamchoom; Anthony Gunawan; Ruishi Zhang; Shusen Xiong (International Journal of Mining Science and Technology, 2025)
Deep-sea mining has emerged as a critical solution to address global resource shortages; however, the mechanical interaction between tracked mining vehicles (TMVs) and soft seabed sediments presents fundamental engineering challenges. This study establishes a multiscale modelling framework coupling the Discrete Element Method (DEM) with Multi-Body Dynamics (MBD) to investigate track-seabed dynamic interactions across three operational modes: flat terrain, slope climbing, and ditch surmounting. The simulation framework, validated against laboratory experiments, systematically evaluates the influence of grouser geometry (involute, triangular, and pin-type) and traveling speed (0.2–1.0 m/s) on traction performance, slip rate, and ground pressure distribution. Results reveal rate-dependent traction mechanisms governed by soil microstructural responses: higher speeds enhance peak traction but exacerbate slip instability on complex terrain. Critical operational thresholds are established—0.7 m/s for flat terrain, ≤0.5 m/s for slopes and ditches—with distinct grouser optimization strategies: involute grousers achieve 35 %––40 % slip reduction on slopes through progressive soil engagement, while triangular grousers provide optimal impact resistance during ditch crossing with 30 %–35 % performance improvement. These findings provide quantitative design criteria and operational guidelines for optimizing TMV structural parameters and control strategies, offering a robust theoretical foundation for enhancing the performance, safety, and reliability of deep-sea mining equipment in complex submarine environments.
Keywords: Soil Mechanics and Vehicle Dynamics; Railway Engineering and Dynamics; Geotechnical Engineering and Soil Mechanics